(untitled) (Baghdad Science Journal, 2025)
New derivative molecular absorption spectrophotometric methods have been developed for the determination of Al (III) , Mn (II) , individually and binary mixtures . The aim of this model of study is to obtain analytical results characterized by adequate standard of analytical figures of merits through application of derivative Spectrophotometry (dnA/d?n). The two metals acetyl acetonates are chemically stable and are widely used as catalysts . Where Interferences are probable due to very close or nearby peaks or Summits, the Zero – Crossing derivative measurement technique is used to avoid interfering effects between two metals pairs.